2012
DOI: 10.1007/s00441-012-1421-9
|View full text |Cite
|
Sign up to set email alerts
|

Different vascular permeability between the sensory and secretory circumventricular organs of adult mouse brain

Abstract: The blood-brain barrier (BBB) prevents free access of circulating molecules to the brain and maintains a specialized brain environment to protect the brain from blood-derived bioactive and toxic molecules; however, the circumventricular organs (CVOs) have fenestrated vasculature. The fenestrated vasculature in the sensory CVOs, including the organum vasculosum of lamina terminalis (OVLT), subfornical organ (SFO) and area postrema (AP), allows neurons and astrocytes to sense a variety of plasma molecules and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
130
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 92 publications
(132 citation statements)
references
References 63 publications
1
130
1
Order By: Relevance
“…Fenestrated capillaries are present in the median eminence, a circumventricular organ, and considerable vascular permeability is observed in the arcuate nucleus (36)(37)(38).…”
Section: Expression Of Socs3 In Agrp Neurons Is Dynamically Modulated Inmentioning
confidence: 99%
“…Fenestrated capillaries are present in the median eminence, a circumventricular organ, and considerable vascular permeability is observed in the arcuate nucleus (36)(37)(38).…”
Section: Expression Of Socs3 In Agrp Neurons Is Dynamically Modulated Inmentioning
confidence: 99%
“…The vascular structure of the NH is unique, as endothelial cells are surrounded by a large perivascular space consisting of two layers of the basement membrane (Morita & Miyata 2012). Double-labeling immunohistochemistry showed that CD31-positive endothelial cells were covered by a large laminin-positive perivascular space (Fig.…”
Section: Effects Of Vegfr and Pdgfr Signaling Inhibition On Vascular mentioning
confidence: 99%
“…The vasculature of adult brains generally contains the blood-brain barrier (BBB) that consists of endothelial cell sheet and tight junction and prevents free entry of blood-derived bioactive molecules into parenchyma (Engelhardt 2003, Abbott et al 2010, Daneman et al 2010. The neurosecretory brain regions, the NH and ME, have fenestrated vasculature that has been defined as a characteristic of the lack of complete BBB and the direct diffusion of neuropeptides into blood circulation (Ciofi et al 2009, Miyata & Morita 2011, Mullier et al 2010, Morita & Miyata 2012.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most fascinating part of the vascular morphology in CVOs is the capillary vessels having fenestrated endothelial cells in all CVOs aside from the SCO (10) . Thus, the blood-brain barrier (BBB) is lacking in all except one: the SCO and, unlike many regions of the brain, there can be bidirectional movement of polar particles between the blood and the neural environments of the CVOs.…”
Section: Introductionmentioning
confidence: 99%